2000
DOI: 10.1161/01.atv.20.8.1990
|View full text |Cite
|
Sign up to set email alerts
|

ApoE Polymorphism and Fish Oil Supplementation in Subjects With an Atherogenic Lipoprotein Phenotype

Abstract: Abstract-The study assessed the efficacy of fish oil supplementation in counteracting the classic dyslipidemia of the atherogenic lipoprotein phenotype (ALP). In addition, the impact of the common apolipoprotein E (apoE) polymorphism on the fasting and postprandial lipid profile and on responsiveness to the dietary intervention was established. Fifty-five ALP males (aged 34 to 69 years, body mass index 22 to 35 kg/m 2 , triglyceride [TG] levels 1.5 to 4.0 mmol/L, high density lipoprotein cholesterol [HDL-C] Ͻ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
177
8
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(198 citation statements)
references
References 68 publications
10
177
8
1
Order By: Relevance
“…This finding is contrary to the reducing effect on small, dense LDL by marine n-3 FA reported in subjects with hypertriglyceridemia (Baumstark et al, 1992;Minihane et al, 2000;Wilkinson et al, 2005). The presence or absence of hypertriglyceridemia could be an important factor for the effect of n-3 FA on small LDL as could the large intake of fish oil in our study, which resembles the one given to healthy subjects in which an increase in LDL apolipoprotein B was reported (Sullivan et al, 1986).…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is contrary to the reducing effect on small, dense LDL by marine n-3 FA reported in subjects with hypertriglyceridemia (Baumstark et al, 1992;Minihane et al, 2000;Wilkinson et al, 2005). The presence or absence of hypertriglyceridemia could be an important factor for the effect of n-3 FA on small LDL as could the large intake of fish oil in our study, which resembles the one given to healthy subjects in which an increase in LDL apolipoprotein B was reported (Sullivan et al, 1986).…”
Section: Discussioncontrasting
confidence: 99%
“…In that case, a similar standardized test meal is to be used in every subject. (Weintraub et al, 1988(Weintraub et al, , 1989Lopez-Miranda et al, 1997Patsch et al, 1992;Mekki et al, 1999;Minihane et al, 2000;Tiret et al, 2000;Sharrett et al, 2001;Robertson et al, 2002;Jackson et al, 2003;Harbis et al, 2004).…”
Section: Aim Of Postprandial Lipaemia Testsmentioning
confidence: 99%
“…Recent evidence (Minihane et al 2000) also suggests that apoE genotype may in part predict the LDLC response to fish oil fatty acid intervention. The variability of LDLCraising effect of EPA and DHA has been frequently reported (Harris, 1997).…”
Section: Apoe Genotype and Responsiveness To Dietary Fat Manipulationmentioning
confidence: 99%
“…The variability of LDLCraising effect of EPA and DHA has been frequently reported (Harris, 1997). In a study of individuals with an atherogenic lipoprotein phenotype (Minihane et al 2000) retrospective genotyping suggests that the LDLC-raising effects observed following supplementation with 3 g EPA + DHA/d are associated with an apoE4 genotype. Additional studies are currently underway to investigate EPA/DHA-LDLC associations.…”
Section: Apoe Genotype and Responsiveness To Dietary Fat Manipulationmentioning
confidence: 99%